Antihyperglycemic activities of protein containing adiponectin from abdominal adipose tissues in the streptozotocin-induced hyperglycemic rats - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani (2017)
Research Problem/Objectives: White adipose tissue is not just an energy storage depot but now it is recognized to be an active organ in energy homeostasis and other physiological functions. It is known to secrete a variety of bioactive proteins known as adipokines. Among these adipokines, adiponectin is reported to have antidiabetic properties which functions as an insulin sensitizer. The present study was performed to evaluate the effects of protein containing adiponectin from abdominal adipose tissues namely chicken, beef & lamb or insulin alone on blood glucose, blood lipid and histological changes in pancreas of streptozotocin-induced hyperglycemic rats.